Existing cattle husbandry practices followed by the farmers in semi-arid region of central Gujarat - KHADDA, B S; LATA, KANAK; KUMAR, RAJ; JADAV, J K (The Indian Journal of Animal Sciences, 2017)
An extensive survey was made to collect the information on cattle husbandry practices followed by the farmers in semi-arid region of central Gujarat through personal interview using a well-structured questionnaire. Majority of cattle keepers practised semi stall feeding system (57.08%) followed by stall feeding (42.92%). The majority of respondents (65.42%) fed readymade concentrate mixture to their animals followed by mixture of home prepared and readymade (28.33%) and home prepared (6.25%). Only 28.75 and 23.75% of the farmers regularly fed common salt and mineral mixture, respectively. Majority (67.50%) of the respondent fed concentrate to lactating cows after the milking and 81.25% respondent fed concentrate mixture as a special ration to their dairy animals during last 2 months of pregnancy. All the respondents followed heat detection practice regularly based upon behavioural signs of estrus, majority (80.00%) of farmers believed on mucus discharge and bellowing as the symptoms of heat. Majority of farmers (90.42%) used artificial insemination for breeding their dairy animals and 80.42% inseminate their cows at mid heat stage. Majority (81.67%) farmers’ believed in quick treatment for anestrous/repeater animals and 69.58% cattle rearers followed pregnancy diagnosis.